Information system and firms' performance : the case of Malaysian Small Medium Enterprises. - Kharuddin, Saira; Mohd Ashhari, Zariyawati; Md Nassir, Annuar (Canadian Center of Science and Education, 2010)
Information systems are widely use by many corporations to automate existing operations and to improve business activities efficiency. Prior researches have shown that information system adoption did increased firms’ performances and operations efficiency. In Malaysia, Small and Medium Enterprises (SMEs) has been targeted as a mechanism in generating domestic-led investment to stimulate economic development, particularly after the economic crisis that hit the country in 1997. Thus, it is crucial for SMEs to adopt information system to enhance their business operations capability and efficiency. Nevertheless, SMEs limited resources to implement information systems have been one of the critical barriers that hindered the adoption of information systems. Malaysian government has allocated special grants and various initiatives to assist Malaysian SMEs to adopt information system software. Therefore, this study is to investigate the impact of accounting information system on firm performance of Malaysian SMEs. Panel data was used to analyse firm’s performance. Results revealed that SMEs adopting accounting information system show significant improvement in performance compared to non-adopters.